2017
DOI: 10.3390/cosmetics4020011
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Ingredients as Emerging Pollutants of Environmental and Health Concern. A Mini-Review

Abstract: Cosmetic and personal care products are used in huge quantities throughout the world; as a result of their regular use, they are continuously released into the environment in very large amounts. Many of these products are biologically active and are characterized by persistence and bioaccumulation potential, posing a threat to ecosystem and human health. On the basis of the most recent scientific literature available on this subject, this paper provides an overview of some cosmetic ingredients that are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
93
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(97 citation statements)
references
References 154 publications
(244 reference statements)
0
93
0
4
Order By: Relevance
“…The presence of pharmaceuticals in surface water presents some levels of risk to aquatic organisms. Most of the pharmaceuticals are biologically active and are characterised by persistence and bioaccumulation potential, posing a threat to the ecosystem and human health (Juliano and Magrini, 2017). Therefore, the aim of this study was to determine the level of occurrence of acetaminophen, amoxicillin, diclofenac and methylparaben in Lagos Lagoon and Ologe Lagoon.…”
mentioning
confidence: 99%
“…The presence of pharmaceuticals in surface water presents some levels of risk to aquatic organisms. Most of the pharmaceuticals are biologically active and are characterised by persistence and bioaccumulation potential, posing a threat to the ecosystem and human health (Juliano and Magrini, 2017). Therefore, the aim of this study was to determine the level of occurrence of acetaminophen, amoxicillin, diclofenac and methylparaben in Lagos Lagoon and Ologe Lagoon.…”
mentioning
confidence: 99%
“…Parabens (esters of p-hydroxybenzoic acid) represent xenobiotics, PPCPs and EDC groups commonly used as preservative in cosmetics and personal care products, food, pharmaceuticals, etc. Although it was found that butylparaben can be synthesised by marine bacteria (Peng et al 2006), only produced synthetically commercial parabens are used for industrial purpose (Juliano et al 2017). Furthermore, for the last 10 years, the EU regulation about paraben content in cosmetic products has been restricted.…”
Section: Introductionmentioning
confidence: 99%
“…According to Regulation (EU) No. 358/2014 (Juliano et al 2017), isopropylparaben, isobutylparaben, phenylparaben, benzylparaben and pentylparaben are prohibited in cosmetic products. As reported by Regulation (EU) No.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum permissible level of this substance is 0.4% in cosmetic products for single ester and 0.8% for their combination (2,3). Parabens can be detected in wastewater, water, sediment, soil, human urine, blood, and adipose tissue (2,(4)(5)(6)(7)(8). Studies conducted in Canada (9), the United Kingdom (10), France (11), and China (12), reported the occurrence of parabens in municipal wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Canada (9), the United Kingdom (10), France (11), and China (12), reported the occurrence of parabens in municipal wastewater. There are studies suggesting that in the conventional WWTPs, these chemicals are not completely removed from the water cycle (8,(13)(14)(15) and this issue remains a challenging problem due to its complex matrices. Over the last few years, the microwave-assisted extraction (MAE) has been found to be a practical method for extracting target compounds from solid matrices (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%